Great Volatility and Great Moderation - Jakob Grazzini; Domenico Massaro (Center for Economic Studies and ifo Institute (CESifo), 2018)
We investigate the sources of the great changes in GDP volatility observed from 1966 to 2000. We develop a general equilibrium model and calibrate it to US data in order to characterize the contribution of micro level productivity shocks, inter-sectoral linkages and households' behavior to aggregate volatility. Our results show that changes in sectoral volatility played an important role in shaping volatility at the aggregate level. Moreover, asymmetries in the economic structure sometimes had an amplifying, and other times a dampening effect on aggregate volatility. We show that the different impact depends on the time-varying correlation between sectoral volatilities and the relative importance of specific sectors in the economy.
Keywords: E32; E23; D57; 330; business cycle; micro-macro volatility; input-output network